The correlation between Self-regulated Learning Behaviors and Academic Classification for HBCU Students Participating in Online and Remote Learning Experiences - Cobb, Jr., Robert; Kuo, Yu-Tung; Faulkner, Paula (European Scientific Journal, ESJ, 2023)
The COVID-19 pandemic placed tremendous pressures on economic, medical, and educational infrastructures and systems around the world. Educational leaders were advised to “shutdown” schools which meant teachers and students were forbidden to gather in the same physical space to deliver and receive instruction. Pressures were transferred to technology leaders to create, maintain, and sustain technology infrastructure that depended on instructional technologies to mediate interactions among students, content, and instructors to provide learners with quality environments, experiences, and services while adhering to social distancing mandates. From a social cognitive perspective, this study is concerned with the relationship between abrupt environmental alteration created by the pandemic and the behavioral implications of deploying motivational and learning strategies empirically proven to contribute to academic success in traditional and online environments. The study showed undergraduate students at an HBCU participating in remote and online learning demonstrated slightly above average self-regulatory strategy use in environmental structuring (3.85), task strategy use (3.26), and time management (3.51). There is a statistically significant correlation between environmental structuring strategy use and academic classification; and a statistically significant correlation between time management strategy use and academic classification. This study does bring attention to environmental conditions of students served by HBCUs; and the implications of these factors on learning behaviors they rely on in technology-mediated learning environments and experiences.